DETERMINATION OF POLYSTYRENE-HYDROCARBON INTERACTION PARAMETERS AND SOLUBILITY PARAMETER USING INVERSE GAS-CHROMATOGRAPHY - OZDEMIR, E; ACIKSES, A; COSKUN, M (Marcel Dekker Inc, 1992)
The weight fraction activity coefficients (a1/w1)infinity and Flory - Huggins X parameters have been determined by using inverse gas chromatography technique over the temperature range of 433-453 K for four hydrocarbons on polystyrene. The Hildebrand solubility parameter delta-2 of polystyrene was then calculated. The values of delta-2 obtained from DELTA-G1BAR infinity and X parameters were found to agree with literature data.
Keywords: Polymer